Revealing the relationship of couples facing prophylaxis of vertical transmission of HIV - Ferreira Langendorf, Tassiane; de Mello Padoin, Stela Maris; Cardoso de Paula, Cristiane; de Oliveira Souza, Ivis Emília; de Moura Bubadué, Renata (Investigación y Educación en Enfermería, 2015)
Objective. To reveal the behavior of couples who face prophylaxis of vertical transmission of HIV. Methodology. This study, based on Heidegger's theory of phenomenology, included 14 participants (7 couples), who received prophylaxis against HIV vertical transmission. The study was conducted from February 2011 to December 2012 in a prenatal outpatient and child care unit at a hospital in the countryside of Rio Grande do Sul, Brazil. Results. Given the possibility of infection and of having a child, the couples revealed the existential movement of staying together to face the situation. The couple learn to take care of themselves in order to be able to care for and become involved with the baby. In this relationship, they teach themselves how to be a family. Conclusion. The inclusion of men in women's health care process, with both serving as a unit, makes it possible to develop assistance in the context of considering the family as being a participant in care. How to cite this article: Langendorf TF, Padoin SMM, Paula CC, Souza IEO, Bubadué RM. Revealing the relationship of couples facing prophylaxis of vertical transmission of HIV. Invest Educ Enferm. 2015; 33(3):